2003
DOI: 10.1074/jbc.m304928200
|View full text |Cite
|
Sign up to set email alerts
|

Golgi Localization of Carbohydrate Sulfotransferases Is a Determinant of L-selectin Ligand Biosynthesis

Abstract: Sulfation of endothelial glycoproteins by the sulfotransferase GlcNAc6ST-2 is a regulatory modification that promotes binding of the leukocyte adhesion molecule L-selectin. GlcNAc6ST-2 is a member of a family of related enzymes that act on similar carbohydrate substrates in vitro but discrete glycoproteins in vivo. We demonstrate that GlcNAc6ST-1, -2, and -3 have distinct Golgi distributions, with GlcNAc6ST-1 confined to the trans-Golgi network, GlcNAc6ST-3 confined to the early secretory pathway, and GlcNAc6S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
28
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 88 publications
1
28
0
Order By: Relevance
“…Consequently, we propose that a portion of the L-selectin ligand remaining in GlcNAc6ST-2 null mice is on core 2 glycans, the sulfation of which is mediated by GlcNAc6ST-1. Consistent with the possibility, de Graffenried and Bertozzi (28) found that GlcNAc6ST-1 preferably modifies the capping group on the core 2 branch rather than that on core 1-extended glycans. Furthermore, Hiraoka et al (47) observed that mice deficient in both GlcNAc6ST-2 and C2GlcNAcT exhibit a greater reduction in lymphocyte homing than GlcNAc6ST-2 single knockout mice.…”
Section: Altered Expression Pattern Of Meca-79 Epitope In Hev Ofsupporting
confidence: 60%
See 1 more Smart Citation
“…Consequently, we propose that a portion of the L-selectin ligand remaining in GlcNAc6ST-2 null mice is on core 2 glycans, the sulfation of which is mediated by GlcNAc6ST-1. Consistent with the possibility, de Graffenried and Bertozzi (28) found that GlcNAc6ST-1 preferably modifies the capping group on the core 2 branch rather than that on core 1-extended glycans. Furthermore, Hiraoka et al (47) observed that mice deficient in both GlcNAc6ST-2 and C2GlcNAcT exhibit a greater reduction in lymphocyte homing than GlcNAc6ST-2 single knockout mice.…”
Section: Altered Expression Pattern Of Meca-79 Epitope In Hev Ofsupporting
confidence: 60%
“…CD34, GlyCAM-1, and MAd-CAM-1) (17,(25)(26)(27). Transfection with cDNA encoding either of the two GlcNAc6STs (GlcNAc6ST-1 and GlcNAc6ST-2) contribute to the formation of sialyl 6-sulfo Lewis X and the MECA-79 epitope on the transfectants (17,25,26,28). We further characterized their substrate specificities and enzymological prop-erties employing protein A-fused GlcNAc6ST-1 and GlcNAc6ST-2 proteins.…”
mentioning
confidence: 99%
“…Carbohydrate sulfation has been shown to be important for the formation of ligands that bind adhesion molecules belonging to the selectin family (4,5). Studies that examine the ability of sulfated carbohydrates to inhibit selectin-ligand recognition also highlight the importance of sulfation to human health.…”
Section: (Gal␤13)galnac␣-o-bn and Gal␤13galnac␣-o-al (Where Al Is mentioning
confidence: 99%
“…Considering the previous finding that both of these sulfotransferases can transfer sulfate onto core 2-branched O-glycans, and our observation that sulfate residues were exclusively present on core 2 branched oligosaccharides of the colonic mucins, the preference for a particular acceptor oligosaccharide structure may not account for the differential activity of GlcNAc6ST-1 and GlcNAc6ST-2 for the colonic mucins. One possible explanation is that the subcellular distribution of GlcNAc6ST-2 is more suitable for transferring sulfate to the GlcNAc-terminated O-glycans of colonic mucins, because GlcNAc6ST-1 is confined to the trans-Golgi network, whereas GlcNAc6ST-2 is distributed throughout the Golgi apparatus (30). Another possibility is that differential preferences of GlcNAc6ST-1 and GlcNAc6ST-2 for the Muc2 core protein, a major colonic mucin, accounts for the difference.…”
Section: Discussionmentioning
confidence: 95%